2006
DOI: 10.1152/ajpcell.00614.2005
|View full text |Cite|
|
Sign up to set email alerts
|

Activation of hypoxia-inducible factor 1 during macrophage differentiation

Abstract: Monocytes/macrophages of the myeloid lineage are the main cellular effectors of innate immunity. Hypoxia-inducible factor 1 (HIF-1) is essential for myeloid cell activation in response to inflammatory stimuli. However, it has not been established whether HIF-1 activity is induced during differentiation from monocyte to macrophage. We demonstrate that macrophage differentiation of THP-1 cells or monocytes from peripheral blood induces increased expression of both HIF-1alpha and HIF-1beta as well as increased HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
83
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 52 publications
8
83
1
1
Order By: Relevance
“…This proposition is in line with the evidence that certain ex vivo myeloid populations (macrophages and neutrophils) are adapted to a hypoxic mode of existence by producing a significant proportion of their ATP through glycolysis (so called "aerobic glycolysis") (13,16). It is also supported by data for the human monocytic cell line THP-1, in which glycolysis is up-regulated following phorbol ester-induced macrophage differentiation, possibly via hypoxia inducible transcription factor-1␣ (59). It would be worthwhile to explore in more detail this concept at the biochemical level.…”
Section: Discussionsupporting
confidence: 76%
“…This proposition is in line with the evidence that certain ex vivo myeloid populations (macrophages and neutrophils) are adapted to a hypoxic mode of existence by producing a significant proportion of their ATP through glycolysis (so called "aerobic glycolysis") (13,16). It is also supported by data for the human monocytic cell line THP-1, in which glycolysis is up-regulated following phorbol ester-induced macrophage differentiation, possibly via hypoxia inducible transcription factor-1␣ (59). It would be worthwhile to explore in more detail this concept at the biochemical level.…”
Section: Discussionsupporting
confidence: 76%
“…42,43 It should be pointed out that phorbol-12-myristate 13-acetate (PMA) was reported to induce increased HIF-1α protein synthesis, but was dispensable in PMA-induced macrophage differentiation of leukemic THP1 cells. 44,45 This discrepancy supported the previous conclusion that different transcriptional factors or signaling molecules are involved in myeloid differentiation. 46 In a previous study we showed that the role of HIF-1α protein in myeloid cell differentiation is independent of its transcriptional activity, because the knockdown of expression of HIF-1β failed to affect HIF-1α-mediated differentiation; 19 HIF-1α protein interacts physically with and enhances the transcriptional activity of C/EBPα and Runx1 proteins and these interactions in turn inhibit the transcriptional activity of HIF-1.…”
supporting
confidence: 73%
“…37 Moreover, the ability to regulate hypoxic gene expression via HIFs is maturationlinked in macrophages. 38 Although dendritic cells accumulate HIF-1␣ in hypoxia, 39 immature forms of this cell type up-regulate other hypoxiaresponsive genes, such as CCL20 via up-regulated p50/p50 NF-B homodimers rather than HIFs. 40 A study of the responses of such related myeloid cell types to identical hypoxic conditions would be interesting but beyond the remit of this study.…”
Section: Discussionmentioning
confidence: 99%